ELearning in Physical Therapy: Lessons Learned From Transitioning a Professional Education Program to Full eLearning During the COVID-19 Pandemic. Issue 4 (4th March 2021) - Ng, Leo; Seow, Kuang Cheng; MacDonald, Laetitia; Correia, Christina; Reubenson, Alan; Gardner, Peter; Spence, Angela L; Bunzli, Samantha; De Oliveira, Beatriz Ito Ramos
Abstract: Objective: The objectives of this cross-sectional qualitative study were to explore the perspectives of students enrolled in one physical therapist undergraduate education program in Australia about their experience with transitioning to full eLearning and student recommendations to improve the learning experience during the COVID-19 pandemic. Methods: Seven focus groups with 28 undergraduate physical therapist students were conducted following the transitioning to full eLearning as a result of strict physical distancing measures. Focus group questions explored the students' experiences of the transition from face-to-face to full eLearning approach and the students' recommendations for improving future eLearning experiences. Data were analyzed using inductive thematic analysis. Results: The 3 themes identified were: (1) students presenting heightened negative feelings such as anxiety, stress, and reduced motivation to study; (2) students continuing to value the face-to-face learning, as it provided social support and facilitated feedback from peers and tutors; (3) student recommendations for eLearning included having online lectures and supplementary videos but face-to-face practical classes and developing healthy learning habits such as scheduled times for studying, exercise, and other activities that regulate stress. Conclusions: The transition to a full eLearning approach in an undergraduate physical therapist education program during the COVID-19 pandemic revealed that students had heightened negative emotions due to the pandemic. Students valued face-to-face practical classes to learn and receive social support from peers and tutors. Student recommendations to future eLearning suggested changes to curriculum development geared toward a greater blended approach to learning. Blended learning may include using online lectures instead of face-to-face lectures and online resources to supplement student learning of practical skills. Impact: As higher education moves toward a more blended approach, lessons learned from this study can help educators design future physical therapist education programs. The findings can also assist programs in delivering a full eLearning approach as the COVID-19 pandemic continues.